Iron-Based Ceramic Composite Nanomaterials for Magnetic Fluid Hyperthermia and Drug Delivery - Ming-Hsien Chan; Chien-Hsiu Li; Yu-Chan Chang; Michael Hsiao (MDPI AG, 2022)
Because of the unique physicochemical properties of magnetic iron-based nanoparticles, such as superparamagnetism, high saturation magnetization, and high effective surface area, they have been applied in biomedical fields such as diagnostic imaging, disease treatment, and biochemical separation. Iron-based nanoparticles have been used in magnetic resonance imaging (MRI) to produce clearer and more detailed images, and they have therapeutic applications in magnetic fluid hyperthermia (MFH). In recent years, researchers have used clay minerals, such as ceramic materials with iron-based nanoparticles, to construct nanocomposite materials with enhanced saturation, magnetization, and thermal effects. Owing to their unique structure and large specific surface area, iron-based nanoparticles can be homogenized by adding different proportions of ceramic minerals before and after modification to enhance saturation magnetization. In this review, we assess the potential to improve the magnetic properties of iron-based nanoparticles and in the preparation of multifunctional composite materials through their combination with ceramic materials. We demonstrate the potential of ferromagnetic enhancement and multifunctional composite materials for MRI diagnosis, drug delivery, MFH therapy, and cellular imaging applications.